(untitled) (Mustansiria Dental Journal, 2018)
This study was conducted to determine clinically if there is a correlation between lengths of upper lip and inter occlusal distance, closest speaking space concening palatal depth relativity and to develop a technique for measuring occlusal vertical dimension. The sample consisted of 88 subjects, irreversible hydrocolloid impressions, stone models, vernier calipers, modified plastic rulers were used in the measurements of lip length, transverse and vertical arch dimensions. The speaking method was used for measuring the free way space by pronouncing m sound while the closest speaking space was measured by asking the subject to pronounce s sound. Statistical analysis was carried out using a standard t-test to compare between males and females; the result reveals possible gender difference related to lip length and palate depth. Also r-test used to find the correlation between the parameters used in the study (lip length, free way space, closest speaking space, inter canine distance, inter molar distance, and palatal depth) , the results analyze and found that there is a positive correlation between the parameters. When selecting a method to be used for OVD measurements, the criteria to be considered are accuracy, repeatability of the measurements and the length of the time required to secure the measurements. The results of this investigation indicate that new method for measuring occlusal vertical dimension may be suggested .It was based on the observed correlation, normally found in individuals with natural teeth, between lip length and different parameters.